Makna Desain Keris dalam Budaya Jawa - Warto Warto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
Cultural objeds in Java besides owning high aesthetic value also have magical energy it is of course to which sure and trusting it. Arlistic to progressively Â form of the objed, hence will be valuable progressively high art and have deeper magical meaning. Keris as oneoi the cultural objed in Java owning very unique desain. Existence of keris cannot be discharged from a smith. Of hands of they keris created. Greatness of keris do not famous only just Java land. But have become heritage grand culture of world. Keris is cultural masterwork of parallel proper Indonesia with other masterpieces of whole world.Â